TOWARD A NEW SOCIOLOGY OF RELIGION. - Fenn, Richard K. (Journal for the Scientific Study of Religion (Wiley-Blackwell))
This paper questions the assumption that religion, or its functional alternatives, inevitably provides the basis for the cultural integration of all societies. In modern societies the process of differentiation has reached the point at which a normative order based on religious beliefs and values is no longer possible. This development, however, coincides with increases in productive capacity which tend to make less difficult the tasks of motivating enough individuals to work and of providing legitimacy for the social order. As a religious basis to the normative order becomes less necessary, religion will continue to have functions for certain strata and for private individuals, but these functions will be more likely to be expressive than utilitarian.